GO/NO-GO PROCEDURE WITH COMPOUND STIMULI: EFFECTS OF TRAINING STRUCTURE ON THE EMERGENCE OF EQUIVALENCE CLASSES. - Grisante, Priscila C.; Galesi, Fernanda L.; Sabino, Nathalí M.; Debert, Paula; Arntzen, Erik; McIlvane, William J. (Psychological Record)
When the matching-to-sample (MTS) procedure is used, different training structures imply differences in the successive discriminations required in training and test conditions. When the go/no-go procedure with compound stimuli is used, however, differences in training structures do not imply such differences. This study assessed whether the go/no-go procedure with compound stimuli with different training structures would produce significant variations in emergent performances. Fourteen undergraduate students were divided into 2 training groups: one-to-many (OTM) and many-to-one (MTO). During training, responses emitted in the presence of compounds defined as Related were reinforced. Responses emitted in the presence of compounds defined as Not Related were not. During tests, new compounds structurally emulated MTS equivalence tests. Participants finished training with comparable numbers of sessions, and 13 showed emergent performances. These results suggest that differences in equivalence test outcomes with different training structures in MTS procedures may be due to their different successive discrimination requirements.